2011
DOI: 10.1142/s1793525311000696
|View full text |Cite
|
Sign up to set email alerts
|

On Closed Leaves of Foliations, Multisections and Stable Commutator Lengths

Abstract: We give examples of foliations that answer two questions posed by Mitsumatsu and Vogt about the genus minimizing properties of closed leaves of 2-dimensional foliations on 4-manifolds. By studying stable commutator lengths in certain stable mapping class groups, we also answer an asymptotic version of another question of theirs concerning bounds on self-intersection numbers of multisections in surface bundles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 16 publications
(27 reference statements)
1
5
0
Order By: Relevance
“…While our results recover some known computations of second bounded cohomology (see e.g. [30,38,6,26]), the previous proofs of these facts rely on a careful analysis of second cohomology, and in doing so they often appeal to deep theorems which are specific to their setting. The advantage of our approach is that it bypasses the cohomological techniques and only focuses on the bounded part.…”
Section: Introductionsupporting
confidence: 71%
“…While our results recover some known computations of second bounded cohomology (see e.g. [30,38,6,26]), the previous proofs of these facts rely on a careful analysis of second cohomology, and in doing so they often appeal to deep theorems which are specific to their setting. The advantage of our approach is that it bypasses the cohomological techniques and only focuses on the bounded part.…”
Section: Introductionsupporting
confidence: 71%
“…While circulating an earlier version of this article, we found out that such an adjunction bound in the case of surface bundles of fiber and base genera g, h ≥ 2 was independently obtained by Bowden [3], where the author studies multisections of surface bundles.…”
Section: Let [S]mentioning
confidence: 73%
“…A sharp upper bound on the self-intersection number of a section of a surface bundle over a surface was originally obtained by Morita in [14], and was later obtained using gauge theory in [2] and [4], respectively. This bound constitutes one side of the inequality leading to the calculation of the precise commutator length of the boundary parallel Dehn twist in Map(Σ 1 g ) [2].…”
Section: Upper Bounds On the Self-intersection Numbers Of Sectionsmentioning
confidence: 99%
“…In [2] it was moreover shown that a similar upper bound holds for Lefschetz fibrations if we remove the absolute value; a proof of which, for sections that miss the critical locus, can be obtained using the above approach and following the framework of [16] for example.) The proof in [2] as well as the one in [4] uses gauge theory, appealing to Seiberg-Witten invariants on minimal symplectic 4manifolds and the adjunction inequality for Seiberg-Witten basic classes. As seen from the above discussion however, the use of gauge theory is rather superfluous.…”
Section: Upper Bounds On the Self-intersection Numbers Of Sectionsmentioning
confidence: 99%